2005
DOI: 10.1016/j.jpainsymman.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Patient-Controlled Analgesia

Abstract: Patient-controlled analgesia (PCA) has become the gold standard for acute pain management since it was first introduced 20 years ago, and its merits have been discussed in quite a large number of publications. This review summarizes the more recent developments, such as new application devices and strategies, including intranasal, spinal, and regional PCA; patient-controlled sedation; experience with children and elderly people; and some data from chronic pain situations. Analyzing PCA literature from 2001 onw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 185 publications
(133 reference statements)
1
36
1
3
Order By: Relevance
“…This is contrary to a previous study done in a group of sickle cell disease patients in whom lower mean morphine consumption in the PCA group resulted in adequate pain relief and significantly less nausea and vomiting compared with the continuous infusion group during vaso-occlusive crises [13]. Recently this trend has changed, as consumption has been found to be equal or more compared to continuous infusion depending upon individual variability [6]. The fact that the amount of pethidine consumed was same in the two groups indicates the advantage offered to IV-PCA group patients, to take the dose of analgesia at the initial feeling of pain, leading to an improved analgesic profile with the same amount of opioid utilized.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This is contrary to a previous study done in a group of sickle cell disease patients in whom lower mean morphine consumption in the PCA group resulted in adequate pain relief and significantly less nausea and vomiting compared with the continuous infusion group during vaso-occlusive crises [13]. Recently this trend has changed, as consumption has been found to be equal or more compared to continuous infusion depending upon individual variability [6]. The fact that the amount of pethidine consumed was same in the two groups indicates the advantage offered to IV-PCA group patients, to take the dose of analgesia at the initial feeling of pain, leading to an improved analgesic profile with the same amount of opioid utilized.…”
Section: Discussioncontrasting
confidence: 67%
“…PCA works on the principle of individual variability of "what you need is what you get" (WYNIWYG) [6]. Since the total amount of pethidine consumed over 24 hours was the same in both groups, one explanation for improved pain control with PCA could be the timing of the doses.…”
Section: Discussionmentioning
confidence: 99%
“…1 Empirical research conducted over the past 20 years has demonstrated several advantages over conventional approaches to acute postoperative pain management. Patient-controlled analgesia is associated with a significant decrease in the incidence of moderate and severe pain after surgery compared with intramuscular opioids.…”
Section: Conclusion : L'utilisation Postopératoire Excessive De Morphmentioning
confidence: 99%
“…In den 3 verfügbaren pädiatrischen Stu dien erweist sich die PCA jedoch als ei [15,23]. Dies wird durch ei ne aktuelle CochraneAnalyse belegt und entspricht den Erkenntnissen zum opio idsparenden Effekt der PCA in der post operativen Schmerztherapie [9,20].…”
Section: Pca Zur Schmerztherapie Bei Mukositisunclassified